Effect of phenylephrine 1.0%–ketorolac 0.3% injection on tamsulosin‐associated intraoperative floppy‐iris syndrome. Issue 9 (September 2018) - Silverstein, Steven M.; Rana, Viren K.; Stephens, Robert; Segars, Larry; Pankratz, Joseph; Rana, Shivani; Juzych, Mark S.; Nariman, Nissiri
Abstract : Purpose : To determine the effect of phenylephrine 1.0%–ketorolac 0.3% injection (Omidria) on different components of intraoperative floppy‐iris syndrome (IFIS). Setting : Silverstein Eye Centers, Kansas City, Missouri, USA. Design : Prospective case series. Methods : Men treated with tamsulosin having standard cataract extraction surgery were placed in a treatment group that received phenylephrine 1.0%–ketorolac 0.3% injection in the irrigation solution and a control group) that received basic saline solution. Every procedure was video recorded using an endocyclophotocoagulation (ECP) probe and microscopic view. Pupil dilation, iris billowing, and iris prolapse were measured using a micrometer, ECP recording grading scale, and microscopic recordings, respectively. Results : Each group (treatment and control) comprised 25 eyes of 25 patients. Although both groups had a decrease in pupil diameter before and after cataract extraction and before cataract extraction and after intraocular lens implantation, the changes were statistically significantly greater in the treatment group. Iris prolapse occurred in 3 patients (12.0%) in the treatment group and 14 patients (56.0%) in the control group ( P < .001). Stage 3 (severe) pupil billowing occurred in 1 eye (4.0%) in the treatment group and 10 eyes (40.0%) in the control group ( P < .001). Conclusions : The use of the phenylephrine 1.0%–ketorolac 0.3% injection combination added to the irrigating solution during cataract surgery in patients at risk for IFIS led to significantly better prevention of miosis, less pupil billowing, and a reduced incidence of iris prolapse. A new grading scale for intraoperative iris abnormalities might be used for future evaluation.